Sosialisasi Cegah Stunting dengan Gerakan Memasyarakatkan Makan Ikan (Gemarikan) di Kabupaten Malang - Aurrel Shafira Kharisma; Elly Kurniawati; Sinollah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2026)
Data shows that until now the Indonesian population is still relatively low in terms of consuming fish compared to other animal foods. GEMARIKAN (Gerakan Memasyarakatkan Makan Ikan) is a national program launched by the Ministry of Marine Affairs and Fisheries starting in 2004 which aims to campaign for the importance of the benefits of eating fish from an early age because of the many nutritional contents contained in fish which are very important for brain growth and intelligence. This activity is themed: Socialization to Prevent Stunting with the Movement to Socialize Eating Fish. The purpose of this activity is to provide knowledge support about the importance of consuming fish in improving the quality of children's growth and development. The targets or targets of this activity are: Stunting families, PKK cadres, Posyandu cadres, pregnant women, breastfeeding mothers, young women (prospective brides). The activity was carried out on May 14, 2024 with a total of 50 counseling participants. The information provided is information about the nutritional content, benefits and importance of consuming fish. It is hoped that children and teachers can find out information about the nutritional content, benefits and importance of consuming fish. The method of implementing this activity is “Socialization” in the form of education which aims to increase understanding in the field of health and related scopes in it so as to make the school community aware of the importance of consuming fish to maintain health and healthy living. The place of implementation is the Wisata Latar Bale Desa Mulyoarjo Kecamatan Lawang. The results obtained were changes in knowledge, actions from the community about the importance of consuming fish, as well as diversification of processed fish foods.